Pet-Keeping in Relation to Asthma, Rhinitis, and Eczema Symptoms Among Adolescents in Kuwait: A Cross-Sectional Study - AlShatti, Khadijah A.; Ziyab, Ali H. (Frontiers in Pediatrics, 2020)
Background: Findings on the associations between household pet-keeping and allergic diseases, including asthma, rhinitis, and eczema, have been contradictory, with investigations reporting positive, negative, and null associations. This study sough to estimate the prevalence of pet-keeping among families in Kuwait and to assess the associations between pet-keeping and symptoms of allergic diseases among adolescents. Methods: Schoolchildren aged 11–14 years (n = 3,864) were enrolled in this cross-sectional study. The children’s parents completed questionnaires regarding their child’s environmental exposures, including pet-keeping in the past 12 months, and clinical history and symptoms of allergic diseases. Associations were assessed using Poisson regression with robust variance estimation, and adjusted prevalence ratios (aPRs) and 95% confidence intervals (CIs) were estimated. Results: Pet-keeping in the past 12 months was reported by 42.8% of the participating families. Birds, cats, rabbits, fish, and dogs were kept by 28.3%, 13.2%, 7.8%, 3.9%, and 3.1% of all households, respectively. Current cat ownership was significantly associated with current wheezing (aPR 1.29, 95% CI 1.05–1.58), current rhinitis symptoms (aPR 1.18, 95% CI 1.02–1.36), and ever doctor-diagnosed eczema (aPR 1.25, 95% CI 1.03–1.50). Current rabbit-keeping was positively associated with multiple symptoms of asthma (e.g., study-defined current asthma: aPR 1.38, 95% CI 1.04–1.82) and eczema (e.g., severe eczema: aPR 1.94, 95% CI 1.02–3.71). Similarly, current bird-keeping was associated with study-defined current rhinitis (aPR 1.19, 95% CI 1.05–1.41) and current itchy rash (aPR 1.27, 95% CI 1.10–1.46). Conclusions: Household pet-keeping is very common and diverse in Kuwait and was found to be positively associated with symptoms of allergic diseases among adolescents. The findings of associations between rabbit-keeping and symptoms of asthma and eczema add to the existing literature and further highlight the importance of considering the pet type when assessing such associations.